2015
DOI: 10.1530/erc-15-0413
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of response to mTOR inhibitors in neuroendocrine tumours

Abstract: Medical treatment of neuroendocrine tumours (NETs) has drawn a lot of attention due to the recent demonstration of efficacy of several drugs on progression-free survival, including somatostatin analogs, small tyrosine kinase inhibitors and mTOR inhibitors (or rapalogs). The latter are approved as therapeutic agents in advanced pancreatic NETs and have been demonstrated to be effective in different types of NETs, with variable efficacy due to the development of resistance to treatment. Early detection of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 93 publications
(89 reference statements)
0
24
0
1
Order By: Relevance
“…The PI3K/AKT/mTOR pathway is constitutively activated in different NETs, including those of pancreatic origin . The expression of mTOR pathway components has been suggested to correlate with clinical behavior and responsiveness to mTOR inhibitors (Righi et al 2010, Qian et al 2013, Zatelli et al 2016. The mTOR inhibitor has recently shown antitumor activity in advanced, well-differentiated and moderately differentiated P-NETs , but resistance to this treatment may develop.…”
Section: :11mentioning
confidence: 99%
See 2 more Smart Citations
“…The PI3K/AKT/mTOR pathway is constitutively activated in different NETs, including those of pancreatic origin . The expression of mTOR pathway components has been suggested to correlate with clinical behavior and responsiveness to mTOR inhibitors (Righi et al 2010, Qian et al 2013, Zatelli et al 2016. The mTOR inhibitor has recently shown antitumor activity in advanced, well-differentiated and moderately differentiated P-NETs , but resistance to this treatment may develop.…”
Section: :11mentioning
confidence: 99%
“…We recently demonstrated that responsiveness to Everolimus in human bronchial carcinoid primary cultures correlates with an active AKT/mTOR signaling pathway (Gagliano et al 2013). However, PI3K/AKT/mTOR signaling does not always predict the sensitivity to mTOR inhibitors and is difficult to assess (Zatelli et al 2016). Therefore, the aim of this study was to investigate the possible predictors of sensitivity to Everolimus in P-NET, to identify patients who may benefit from treatment avoiding useless side effects in resistant patients.…”
Section: :11mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the role of various predictors of response to mTOR inhibitors, including clinical, biological, and histological factors (Zatelli et al 2016).…”
Section: Predictive Factors Of Response To Everolimusmentioning
confidence: 99%
“…It is therefore not surprising that somatostatin analogs (SSAs) are active in the treatment of a broad spectrum of NETs [5]. Likewise, the mammalian target of rapamycin (mTOR) pathway is upregulated in a large percentage of NETs regardless of primary site, even though mutations in the mTOR pathway are observed almost exclusively in pancreatic NETs [6]. Indeed, recent clinical trials demonstrate that mTOR inhibition is an appropriate strategy for treatment of both pancreatic and nonpancreatic NETs [7,8 && ].…”
Section: Introductionmentioning
confidence: 99%